Ethyl Maltol as a New Ligand forSpectrophotometricDetermination of Iron: Determination of iron - Jafarian-Dehkordi, Abbas; Rajabzadeh, Shahriar; Saghaei, Lotfollah (Iranian Journal of Pharmaceutical Sciences, 2007)
In this study a new simple selective and sensitive spectrophotometric procedurefor determination of Fe(III) is described. It is based on the formation of a coloredcomplex between ferric iron and ethyl maltol, a strong and highly selective ligandfor Fe(III). After mixing sample and reagent, and incubating at the room temperature,Fe(III)-ethyl maltol complex was extracted with different solvents and the absorbancewas measured at 395 nm. The effect of analytical variables, i.e. amount and typeof the reagents, pH, ratio of Fe(III)/ethyl maltol, presence of other ions, etc., in thedetermination of iron were studied. Our findings showed that the optimum wavelengthfor the measurement was 395 nm. The optimum condition for complex formationand determination of Fe(III) were: molar ratio of ethyl maltol/Fe(III) = 6-10; pH =5. The best solvent for extraction was chloroform. Under the recommendedconditions, formation of the complex is completed in less than 2.5 h. Limit of detectionwas found to be 2.5×10-6M of Fe(III). Linear regression (r2=0.9998) was observedover the range of 2.5×10-6to 5×10-4M of the Fe(III) with respect to the complexnominal concentration. Ions commonly associated with iron did not interfere in thepresent method. This is a simple, reproducible, and sensitive method for determinationof Fe(III) in μmolar levels.